Alternative careers in science (Elsevier, 2006)
Alternative Careers in Science:Leaving the Ivory Tower is a concise desciption of the many option avail - able to those interested in science and wondering if a way to earn a living while satisfying their curiosity. The Writing style is personnal enough to be interesting to the public and concise enoung to appeal to scientist.